Dynamic simulation and virtual reality in hydrology and water resources management - Teegavarapu, Ramesh S. V., 1970-; Chandramouli, Chandramouli V. (Boca Raton, FL : CRC Press, 2021)
"This covers system dynamics simulation and virtual reality modelling applied to the spatial and temporal behavior of natural and managed water resource systems, such as water demand and supply allocations, flooding, and the interactions between different types of water"--
Simulation and systems dynamics approach -- Building water and environmental system dynamics simulation models -- System dynamics models : applications -- Simulation models with animation -- Basics of virtual reality modelling -- Virtual reality applications.
OCLC-licensed vendor bibliographic record.
Keywords: Watershed management -- Data processing; Water resources development -- Data processing; Hydrologic models; Virtual reality; SCIENCE / Environmental Science